PERSEPSI PETANI BALI TERHADAP KUT YANG DISEMPURNAKAN - I D. P. OKA SUARDI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2000)
There are many problems on farm credit distribution, such as: absorptionlevel is low, credit arrears, and undicipline of personels. In anticipation, thescheme of the credit has been revised, to involve: credit interest, credit plafonds,bank as a channeling agent, village cooperative unit as an executing agent, andthe participation of NGOs.The aim of this research was to identify the perception of farmers aboutthe farm credit that has been revised. Porposive sampling method was used todetermine the location and samples. Survey method was employed in the datacollection, and data analysis used description method.The perception of the farmers was that: credit conditions are accepted, thecredit interest is low, plafonds of the credit is enough to cost the farming, andcredit realization is late. Based on these results, it is suggested that the creditpersonels increase their performance so that credit distribution will besuccessful.